Implementation of Wakalah wal Murabahah Financing in Improving the Quality of Life of Underprivileged Women - Fera Ananda; Yoni Hendarawan; Mikhral Rinaldi; Darlin Rizki (University of Darusssalam Gontor, 2025)
Although Islamic microfinance institutions adopt wakalah and murabahah contracts to empower underprivileged women, challenges remain regarding their conformity with sharia principles, members’ limited understanding of the contracts, and difficulties in the joint liability mechanism. This research aims to examine the implementation of the wakalah and murabahah contracts within the Islamic microfinance scheme applied by Koperasi Mitra Dhuafa (KOMIDA) Meulaboh branch, as well as their impact on the economic empowerment of underprivileged women. This research employed a qualitative approach with a case study design at KOMIDA Meulaboh. Data were collected through interviews, participatory observation, and document analysis, and subsequently analyzed using the Miles and Huberman model, which consists of data collection, reduction, presentation, and conclusion drawing. The validity of the data was ensured through source and method triangulation. The findings reveal that the implementation of wakalah and murabahah contracts at KOMIDA Meulaboh generally adheres to sharia principles, although in practice certain dynamics affect their conformity. The financing process extends from member recruitment to loan repayment, with several technical adjustments that have implications for the contractual form. Nevertheless, this financing scheme has been proven to increase income, strengthen microenterprises, and empower underprivileged women, despite limited understanding of the contracts and challenges in the joint liability mechanism. These contracts have the potential to serve as instruments of empowerment, however, their effectiveness largely depends on sustained mentoring, Islamic financial education, and compliance with fiqh muamalah principles.